2023
DOI: 10.3390/pr11051570
|View full text |Cite
|
Sign up to set email alerts
|

Study on Internal Flow Characteristics and Abrasive Wear of Pelton Turbine in Sand Laden Water

Yu Huang,
Fangxiong Deng,
Huiming Deng
et al.

Abstract: When a Pelton turbine operates in sand laden water, the abrasive wear of its overflow components by high-speed jets is serious. Based on the VOF (volume of fluid) multiphase flow model, the SST (shear stress transfer) k-ω turbulence model, the particle motion Lagrangian model, the generic wear model, and the SIMPLEC (Semi-Implicit Method for Pressure Linked Equations Consistent) algorithm, the liquid–air–solid three-phase flow in the key overflow components of a Pelton turbine were simulated, the abrasive wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Kenichi et al [28] explored the effects of the attack angle and a material's hardness on wear through jet wear tests on a range of materials and coatings. By using the Euler-Lagrange method, Liu [29] and Huang [30] studied the sediment wear mechanism of the flow parts of the impact turbine and found that the sediment speed caused severe wear and erosion on the jet mechanism and the bottom of the bucket blade of the impact turbine from the perspective of sediment concentration and the operating conditions. At the same time, Deng [31] found that the jetting needle of the impact turbine was offset after wear, causing the jet water to be unable to uniformly shoot into the bucket, resulting in unbalanced radial and axial forces on the impact turbine runner, and the unit stability decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Kenichi et al [28] explored the effects of the attack angle and a material's hardness on wear through jet wear tests on a range of materials and coatings. By using the Euler-Lagrange method, Liu [29] and Huang [30] studied the sediment wear mechanism of the flow parts of the impact turbine and found that the sediment speed caused severe wear and erosion on the jet mechanism and the bottom of the bucket blade of the impact turbine from the perspective of sediment concentration and the operating conditions. At the same time, Deng [31] found that the jetting needle of the impact turbine was offset after wear, causing the jet water to be unable to uniformly shoot into the bucket, resulting in unbalanced radial and axial forces on the impact turbine runner, and the unit stability decreased.…”
Section: Introductionmentioning
confidence: 99%